Growth Inhibition Test of Gram and Negative Bacteria in Pharmaceutical Biotechnology Products in the Form of Hand Sanitizer Formulations Based Fermented Telang Flower Kombucha - Hari Hariadi; Muhammad Andry; Muhammad Amin Nasution; Ade Sumiardi; Firman Rezaldi; Suseno Amien; Yusep Ikrawan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Telang flower kombucha is proven to have various pharmacological activities, so that it can be developed as medicines, cosmetics, and its waste can be applied in agriculture as an ingredient in organic liquid fertilizer to support plant development and growth. This research aims to make hand sanitizer gel formulations and preparations with active butterfly pea flowers. Disk diffusion is used to stop gram-positive and gram-negative bacteria from growing. Post hoc analysis and one-way ANOVA were used to analyze the data. The one-way ANOVA analysis yielded results with a significance level of P<0.05, allowing the post hoc test to continue. When tested at a sugar concentration of 40%, the butterfly pea flower kombucha hand sanitizer significantly outperformed the control when it came to inhibiting the growth of the test bacteria. The best way to stop the test bacteria from growing is to use a concentration of 40%.